The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1124/mol.64.3.610
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein Exports Sulfated Estrogens but Not Free Estrogens

Abstract: Breast cancer resistance protein (BCRP), an ATP-binding cassette transporter, confers resistance to a series of anticancer reagents such as mitoxantrone, 7-ethyl-10-hydroxycamptothecin, and topotecan. We reported previously that estrone and 17␤-estradiol reverse BCRP-mediated multidrug resistance. In the present study, we demonstrate that BCRP exports estrogen metabolites. First, we generated BCRP-transduced LLC-PK1 (LLC/BCRP) cells, in which exogenous BCRP is expressed in the apical membrane, and investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
127
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 16 publications
10
127
2
3
Order By: Relevance
“…The latter authors also suggested that 17␤-estradiol is a transported substrate of human BCRP. This conclusion, however, conflicts with the report of Imai et al (2003) that found that BCRP transports only sulfated conjugates of estrone and 17␤-estradiol but not free estrogens.…”
contrasting
confidence: 54%
“…The latter authors also suggested that 17␤-estradiol is a transported substrate of human BCRP. This conclusion, however, conflicts with the report of Imai et al (2003) that found that BCRP transports only sulfated conjugates of estrone and 17␤-estradiol but not free estrogens.…”
contrasting
confidence: 54%
“…BCRP transports certain chlorophyll metabolites, steroid metabolites and xenobiotics and is presumed to play a protective role against toxic substances in the maternal-placental barrier, the digestive tract and the blood-testis barrier (12)(13)(14)(15). BCRP is a molecular determinant of side-population (SP) cells, which are enriched in various stem cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 ABCG2 is a half-transporter, exhibiting a broad substrate specificity for various anticancer agents, including mitoxantrone, anthracyclines, and camptothecins. 14,15,16 It is implicated in the transport of endogenous compounds, for example, sulfate conjugates of estrogen, 17 and its expression can be modified by estrogen. 18 Expression of the transporter also protects against a certain form of porphyria characterized by severe phototoxicity, which was observed in ABCG2 knockout mice after exposure to a diet rich in the chlorophyll-derived phototoxin pheophorbide and UV light.…”
mentioning
confidence: 99%